Mortality experience among employees at a hydrometallurgical nickel refinery and fertiliser complex in Fort Saskatchewan, Alberta (1954–95). Issue 11 (1st November 2001) - Egedahl, R; Carpenter, M; Lundell, D
Abstract : OBJECTIVE: To study the mortality experience of workers at a hydrometallurgical nickel refinery and fertiliser complex in Fort Saskatchewan, Alberta, Canada. METHODS: A total of 1649 male employees of Sherritt International who worked for at least 12 continuous months during the years 1954 to 1978 at the Fort Saskatchewan, Alberta hydrometallurgical nickel refinery and fertiliser complex were followed up for an additional 17 years. Mortality was ascertained from the Canadian mortality data base maintained by Statistics Canada and covered the years 1954–95. Statistics were analysed with Monson's computer program. RESULTS: Total mortality, when compared with the Canadian population, was significantly below expectation. Fewer deaths were found for circulatory disease, ischaemic heart disease, respiratory disease, neoplasms, digestive cancer, and accidents, poisonings, and violence. Among the 718 men in the group exposed to nickel, there were no deaths due to nasal cavity or paranasal sinus cancer. Fewer deaths were found for all causes, circulatory disease, ischaemic heart disease, neoplasms and digestive cancer. Lower death rates were observed than expected for respiratory malignancies and cancer of the bronchus and lung. CONCLUSION: No association was found in this study between exposure to nickel concentrate or metallic nickel in the hydrometallurgical refining process and the subsequent development of respiratory cancer.